On Research-Minded Practitioners: A Response to McBeath and Austin. (July 2015) - Yaffe, Joanne
McBeath and Austin define the concept of research-minded practitioners, describe the organizational contexts, structures, and strategies for supporting this type of practitioner. Further, the authors propose a research agenda to establish effective organizational development strategies to support research-minded practitioners, align their efforts with organizational improvement processes, and culminate in new directions for practice research. This response to McBeath and Austin disagrees with their characterization of evidence-based practice, their definition of practice research, and their conceptualization of the research-minded practitioner as something different from an evidence-based practitioner. While McBeath and Austin are commended on their analysis of organizational barriers to research-minded practice, the redundancy of the concept of research-minded practice is questioned by reiterating commonly held definitions of evidence-based practice.